IDENTIFIKASI Fasciola hepatica PADA SAPI DI SLEMAN YOGYAKARTA - Desi Ranika; Nunung Sulistyani (Universitas Lambung Mangkurat, 2024)
Due to the economic value of beef cattle and dairy cattle, efforts need to be made to increase and prevent Fasciola hepatica infection. Fasciola hepatica infection in cattle can cause losses. This research aims to identify Fasciola hepatica in cattle in Sleman DI Yogyakarta. Identification of Fasciola hepatica is carried out by microscopic examination of feces using the formol-ether sedimentation method. Data analysis was carried out descriptively. Data are presented in the form of prevalence tables and images of Fasciola hepatica eggs. As many as 50% of male cattle and 50% of female cattle aged more than 12 months have Fasciola hepatica infection. Fasciola hepatica infection in cattle in Sleman DI Yogyakarta is 20% .